Asuhan Kebidanan Pada Ibu Hamil Dengan Anemia Ringan Di PMB Nurhayati Wilayah Kerja Puskesmas Air Tiris 2024 - Mawaddah, Jannatul; Apriyanti, Fitri (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Anemia is one of the problems in pregnancy, a mother who experiences mild anemia during pregnancy will have a bad impact on herself and also the mother's fetus, such as causing abortion, premature labor, stunted growth and development of the fetus, during childbirth it can cause premature rupture of membranes (PROM) and can also cause hiss disorders and lack of strength when pushing. The aim of the research is to provide Midwifery Care to Pregnant Women with Mild Anemia in the PMB Nurhayati Working Area of the Air Tiris Community Health Center on 10 June - 23 June 2024. The results of the case study research given to Mrs. F with 14 home visits in 2 weeks, namely the mother's hemoglobin level is normal. Midwifery care is provided in the form of providing PENKES (health education) to the mother about the dangers of anemia in pregnancy and also encouraging the mother to maintain her diet and eating nutritious food, encouraging the mother to regularly consume Fe tablets, and also giving the mother green bean porridge twice a day for 14 days. Based on care for pregnant women carried out on Mrs. F aged 20 years G1P0A0H0, it was found that the hemoglobin level in the mother was normal. The conclusion is that the care provided was carried out well and had satisfactory results. It is hoped that subjects and the public can increase knowledge about pregnancy, especially regarding knowledge and treatment of mild anemia in pregnancy.